A Visual Dashboard for Moving Health Technologies From "Lab to Village" - Masum, Hassan; Singer, Peter A (JMIR Publications, 2007)
New technologies are an important way of addressing global health challenges and human development. However, the road for new technologies from "lab to village" is neither simple nor straightforward. Until recently, there has been no conceptual framework for analyzing and addressing the myriad forces and issues involved in moving health technologies from the lab to those who need them. Recently, based on empirical research, we published such a model. In this paper, we focus on extending the model into a dashboard and examine how this dashboard can be used to manage the information related to the path from lab to village. The next step will be for groups interested in global health, and even the public via the Internet, to use the tool to help guide technologies down this tricky path to improve global health and foster human development.